Design and implementation of an information system for self-control of bronchial asthma by patients - Glinka, Konrad; Melnyk, Anatoly (Lviv Politechnic Publishing House, 2020)
The aim of this article is to develop information system for people with bronchial asthma. The main function of the information system described in the article is enabling self-control of bronchial asthma by patients. By controlling asthma correctly, patients can reduce the symptoms of asthma. The most important task solved before the information system design was a selection of the asthma parameters which can be monitored and implemented in it. The information system consists of two main elements: a database and an application. The article describes the technologies used to create these elements. Moreover, the article provides information about connection between the database and the application. The article also includes basic information about asthma and describes the information system work.
Keywords: asthma control, asthma parameters, application, database, Java, JDBC, medical informatics, information system